Chemical Interventions to Alleviate Salt Stress in Cotton Plants: A Review - Akmal , M Asrorov; Ibrokhim, Y Abdurakhmonov; Zabardast, T Buriev; Ildiko, Matusikova; Naim, N Khusenov; Ilhomjon, Bozorov; Akramjon, Mamajanov; Sardor, Narmatov; Mukhtor, M Darmanov; Mirzakamol, Ayubov (Plant Science Today, 2023)
The alleviation of salt stress in cotton plants through the application of exogenous chemicals has emerged as a viable strategy to mitigate the adverse effects on various plant attributes, including growth, development, yield, and flowering. Plant hormones, known for their efficacy at low doses, have garnered significant attention in this context. Despite being inherently susceptible to salt stress, cotton plants experience severe impediments in water absorption from the soil, leading to delayed growth and development. Several phytohormones, including jasmonic acid, salicylic acid, and glycine betaine, have been extensively investigated in numerous studies for their potential to ameliorate salt stress in cotton plants. Promising results have been obtained with both foliar and seed treatments employing these substances. This foundational knowledge has paved the way for the development of alternative strategies to mitigate salt stress. However, the practical utilization of these chemicals is hindered by their elevated cost. Plant growth regulators, such as nitric oxide and melatonin, have also garnered interest for their ability to alleviate salt stress in cotton plants. Numerous studies have corroborated their effectiveness in this regard. This review comprehensively examines the aforementioned substances and extracts that have been investigated for their potential to mitigate the detrimental effects of salt stress on cotton plants.